(untitled) (World Economics and Finance Bulletin, 2024)
This study aims to determine the role of ecosystem accounting in the process of reducing environmental costs. To achieve the goal of study. The Researchers presented the problem of study and previous studies related to ecosystems. Ecosystem accounting. Researchers also presented some previous studies on cost management tools. The Researchers focused on cost management tools that have the greatest impact on reducing environmental costs, and their impact on achieving environmental system integration. In order to determine the relationship between ecosystem accounting and environmental costs.